What is the vertex form of f(x) = -x^2 + 3x-2 ?

1 Answer
Jul 24, 2016

f(x)=-x^2 +3x-2=(-x+1)(x-2)

Explanation:

f(x)=-x^2 +3x-2=(-x+1)(x-2) You can use foil to check that it's correct.
Let f(x)=ax^2 +bx+c
My thought process behind this, was:
Since in ax^2 a is a negative value, one of the factors will have to be negative when using foil.
Same goes for c
Finally, since b was positive, that means that I have to arrange the bx and c in a manner that will get me a positive, i.e. (-x)\times(-y)=+(xy).